Analisis Implementasi Contractor Safety Management System (CSMS) Terhadap Pekerjaan Berisiko Tinggi di PT Pertamina (Persero) Refinery Unit IV Cilacap - Kusuma Damayanti Santoso; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
Contractor Safety Management System (CSMS) is a system that manage occupational safety contractor in site of business. Job is auctioned to contractor has three risk category is low category, medium category and high category. In 2011 and 2013, PT Pertamina (Persero) Refinery Unit IV Cilacap had been accidents at high risk jobs that result in death. In the implementation of CSMS at PT Pertamina (Persero) Refinery Unit IV Cilacap ever there is a discrepancy with CSMS guidelines that contractors borrow PPE owned by PT Pertamina (Persero) Refinery Unit IV Cilacap. While there is an agreement in the pre-qualification stage the contractor will provide PPE in any kind of job. The purpose of this study is to analyze the implementation of CSMS in high-risk jobs in accordance with the guidelines CSMS PT Pertamina ( Persero ) Refinery Unit IV Cilacap. The research is a qualitative descriptive analysis method is done by in-depth interviews and field observations. The subjects of this study consists of 4 main informants and 2 triangulation  informants. The results showed most of the implementation of CSMS in high-risk jobs are in accordance with the guidelines CSMS, but not all of the work assessed the risks, the kick off meeting materials are incomplete, the orientation of job sites only in certain locations, there are unsafe act and unsafe condition, there has been no communication on the final evaluation. It is necessary to hold discussions after work is completed.